A simplified method for parameters calibration of the new local approach model for cleavage fracture in a ferritic steel. (April 2019) - Shen, Airu; Li, Peichao; Wang, Keyong; Qian, Guian; Berto, Filippo
Highlights: Effect caused by m and σ 0 hardly change with λ under different temperatures. Calibrated failure probability is close to the experimental result when taking λ = 1.5 . A simple approach to calibrate the local approach has been proposed. Abstract: This work presents a simplified method for parameters calibration of the new local approach model (NLAM) for cleavage fracture in a ferritic steel. Based on the Beremin model, a NLAM was recently proposed by Lei (2016) to calculate the Weibull parameters. Although the above NLAM proves to be mathematically and physically self-consistent, yet there are still no reliable and convenient methods to calibrate the model parameters. Considering the plastic volume is determined by the threshold coefficient of fracture process zone λ, we adopt four different values of λ in this work to calculate the plastic volume so as to obtain four groups of calibrated Weibull parameters. The material used in this study is the pressure vessel steel 20MnMoNi55 with some published strength data under two subzero temperatures. And the finite element analysis FEA) software ABAQUS is employed to obtain the stress distributions, then the calibration results for four different values of λ are compared and analyzed. These efforts show that taking λ = 1.5 is a more reasonable and reliable choice.